2007
DOI: 10.1007/s10517-007-0052-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress in patients with chronic heart failure and type 2 diabetes mellitus

Abstract: Parameters of oxidative stress were studied in patients with chronic heart failure and/or type 2 diabetes mellitus. Chronic heart failure was accompanied by severe oxidative stress, while in patients with type 2 diabetes mellitus the signs of oxidative stress were less pronounced. The intensity of free radical oxidation in patients with chronic heart failure and type 2 diabetes mellitus was not higher compared to patients with chronic heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Previously it was demonstrated that oxidative stress under hyperglycemic conditions promotes lipid infiltration to the vascular wall caused by increased oxidation of lipoproteins [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Previously it was demonstrated that oxidative stress under hyperglycemic conditions promotes lipid infiltration to the vascular wall caused by increased oxidation of lipoproteins [12] .…”
Section: Discussionmentioning
confidence: 99%
“…Several groups have reported increased lipid peroxidation and carbonyl stress in the cardiovascular system of diabetic patients (Arzamastseva et al, 2007; Anderson et al, 2009; Annadurai et al, 2014). Studies in diabetic rat heart show that HNE binds preferentially to cysteine > histidine > lysine residues in the mitochondria (LoPachin et al, 2009).…”
Section: Cardio-metabolic Disease and Oxidative Stress In Striated Mumentioning
confidence: 99%
“…The results show that antioxidant capacity in terms of the CUPRAC assay were significantly higher in both phases of roasted seed extracts compared to those of raw seed extracts (p<0.05), resulting also in a significantly higher antioxidant capacity in roasted compared to those of raw seeds in total (p<0.05). Oxidative stress plays an important role in ageing and the pathogenesis of chronic diseases such as atherosclerosis and diabetes (Arzamastseva et al, 2007;Giacco & Brownlee, 2010). Many epidemiological studies suggest that consumption of a fruit-and vegetable-rich diet inversely correlates with the risk of chronic diseases.…”
Section: Cuprac Assaymentioning
confidence: 99%